The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1021/acs.chemmater.6b02334
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Synthesis of Atomically Thin 1T-TaS2 for Tunable Charge Density Wave Phase Transitions

Abstract: The charge density wave (CDW) in twodimensional (2D) materials is attracting substantial interest because of its magnificent many-body collective phenomena. Various CDW phases have been observed in several 2D materials before they reach the phase of superconductivity. However, to date, the atomically thin CDW materials were mainly fabricated by mechanically exfoliating from their bulk counterparts, which leads to low production yield and small sample sizes. Here, we report the controlled synthesis of atomicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(79 citation statements)
references
References 38 publications
2
73
3
1
Order By: Relevance
“…Chemical vapor deposition (CVD), chemical vapor transport (CVT), and MBE have been successfully used to synthesize CDW or SC transition metal dichalcogenide monolayers and few‐layers ( Figure ), including TiSe 2 , TaS 2 , TaSe 2 , NbSe 2 , NbS 2 , and so on. For example, Liu and co‐workers have reported CVD synthesis of 2 H ‐NbSe 2 monolayer with robust SC ( T SC ≈ 0.8 K) .…”
Section: Recent Progress On the Synthesis Of 2d Phase‐transition Matementioning
confidence: 99%
“…Chemical vapor deposition (CVD), chemical vapor transport (CVT), and MBE have been successfully used to synthesize CDW or SC transition metal dichalcogenide monolayers and few‐layers ( Figure ), including TiSe 2 , TaS 2 , TaSe 2 , NbSe 2 , NbS 2 , and so on. For example, Liu and co‐workers have reported CVD synthesis of 2 H ‐NbSe 2 monolayer with robust SC ( T SC ≈ 0.8 K) .…”
Section: Recent Progress On the Synthesis Of 2d Phase‐transition Matementioning
confidence: 99%
“…CVD involves chemical reactions of gaseous reactants on a heated substrate surface [54,55]. The CVD approach has been used successfully in synthesizing 1T-VS 2 [56,57], 1T-VSe 2 [58,59], 2H-NbS 2 [60], 3R-NbS 2 [60], 2H-NbSe 2 [61], 1T-TaS 2 [62,63], 1T-TiSe 2 [64], and so on. Contamination-free and high crystalline quality samples with potential for scaling-up are the great advantages of the CVD method [65].…”
Section: Chemical Vapor Depositionmentioning
confidence: 99%
“…Later, W. Fu et al reported the controlled synthesis of atomically-thin 1T-TaS 2 [62] ( Figure 6). The tantalum pentachloride (TaCl 5 ) and sulfur (S) powder were used as precursors.…”
Section: Chemical Vapor Depositionmentioning
confidence: 99%
“…With increasing interest in studying monolayer or fewlayer charge density wave TMDs, the bottom-up approach of growth by molecular beam epitaxy (MBE) [13,19] or chemical vapour deposition (CVD) [15,16] techniques has become common. Once optimized, these methods are excellent at producing thin films.…”
Section: Introductionmentioning
confidence: 99%